New species of Elampus Spinola, 1806 (Hymenoptera: Chrysididae), with a key to the Neotropical species of the genus - Lucena, Daercio A. A.; Gomes, Rayane S. (Zootaxa, 2016)
Three species of Elampus Spinola are reviewed. A new species, Elampus macuxi Lucena, sp. nov. (Brazil, Roraima) is described and illustrated. The lectotype is designated for Elampus aequinoctialis Ducke 1901. A key for three Neotropical species is given.